(untitled) (Research, Society and Development, 2020)
The inoculation with bacteria of the genus Bradyrhizobium, causes in the rhizosphere the specialized formation in the biological qualification of nitrogen, being discarded the application in the soybean culture, since in relation to the symbiotic it obtains to supply its needs. The objective of the work was to evaluate the influence of inoculation as well as nitrogen levels in coverage on soybean growth, development and productivity. The experiment was carried out in the experimental area of the State University of Mato Grosso do Sul - University Unit of Aquidauana. The experimental design was in randomized blocks in a 4x4 factorial scheme, with four replications. The treatments consisted of a combination of inoculants (Bradyrhizobium japonicum; Azospirillum brasilense; B. japonicum + A. brasilense; Control without inoculation) and four levels of nitrogen in soybean coverage (0; 50; 100; 150 kg ha-1). The inoculation was carried out before sowing, since the application of nitrogen was taken on state V8, for that, ammonium sulfate was used as the source. The following were provided: final plant population, plant height, height of insertion of the first pod, stem diameter, number of pods per plant, number of grains per pod, grain yield, mass of 1000 grains. The inoculation of soybean seeds using alone or together does not interfere in the development and productivity of grains in the soybean culture, as well as the use of mineral nitrogen in cover is not necessary, o it does not reflect in increments in the productivity of soybeans.